An approach to the trend of film on art in post-revolutionary Cuba - Cossalter, Javier (Nawi, 2022)
This article explores the trend of film on art in Cuba after the Revolution, with the purpose of unraveling the aesthetic and political implications of the link between cinema and the visual arts. To do this, after raising the panorama of film on art in Latin America during the modernization of cinema, the post-revolutionary Cuban cultural context is approached to observe the creation of new entities for the promotion and dissemination of innovative artistic and cultural practices. In this sense, the Cuban Institute of Cinematographic Art and Industry promoted the making of documentary short films that approached art and local culture from an intermediary and experimental perspective that transcended the simple propaganda tone. Ultimately, we proceed to the textual and pragmatic analysis of two short paradigmatic films, with the interest of elucidating their expressive and communicational features, and establishing the patrimonial nature of these audiovisual productions.